Growth Performance of Pangasius sp Fed Different Types of Diets Formulated from Varieties Fish Meal Sources - Khamsiah Ahmad; Aras Syazili; Surahman Surahman; Mutmainnah Mutmainnah (Techno: Jurnal Penelitian, 2022)
Pangasius sp is an introductory species that is widely distributed in freshwater regions in Indonesia since the 1990s and it was initiatively reared at the beginning of 2011 using a floating net cage in Lake Ngade, Ternate. Even though it has benefited economically, there is still a lack of information on its biological and ecological aspects. Growth and survival rate are two main factors that should be known to develop Pangasius aquaculture. The study aims to understand the growth and survival rate of Pangasius by mixing different fish meals into dietary. 120 Pangasius fingerlings were placed into 12 tanks. Diet was formulated using Pearson’s square method. Three different protein fish meal sources were mixed into feed formulation namely flying fish meal, Nile meal, and eel meal. Commercial feed was used as control. Filling Randomized Design (FRD) was applied with the experimental set-up of the treatments. The results show that feed stability in water ranges from 2'23" to 3'47" while feed durability ranges from 2'09" to 2'35". The survival rate of Pangasius is almost 100% except for treatment C. Growth rates vary among treatments which is the highest found in treatment A (16.42%) followed by treatment B (15.85%), D (15.57%), and C (7.00%) respectively. Nile fish meal is also significantly affected (P<0.05) by the Specific Growth Rate (SGR) of fish. Nutrition ingredients and water quality parameters are conducive to maintaining the fish's life. All in all, different fish meal sources in the formulated diet are significantly supporting Pangasius growth.